Textual Analysis of Quality Assurance Development in Bosnia and Herzegovina’s Higher Education Sector - Figurek, Aleksandra; Cirella, Giuseppe T.; Goncharuk, Anatoliy G.; Iortyom , Enoch T.; Vaskovic, Una; Abebe , Solomon T. (Acta Paedagogica Vilnensia, 2022)
Education is the bedrock of any nation. It is essential for individual and societal growth and development. This study investigates the role of quality assurance in achieving the expected outcome of education in Bosnia and Herzegovina’s higher education sector. A textual analysis is used to examine the National Qualification Framework. The study is based on a documented review and descriptive analysis of student enrollment and programs of studies. The textual analysis is largely qualitative in nature. Unlike the global trend, it can be seen that student enrollment is on the decline in Bosnia and Herzegovina. It was found that quality assurance is an indispensable tool for strengthening the higher education sector and for achieving the desired change and outcomes that education offers. It was also found that study programs and curricula are pivotal for teaching and learning processes, and that a unified qualification framework is essential for achieving set objectives of education at all levels. The study recommended that sound quality assurance systems as well as an appropriate structure for monitoring and accreditation be put in place and be judiciously followed in order to achieve the desired outcomes in conjunction with the set objectives of higher education in the country. Moreover, certain pressures (i.e., democratic, economic, and systemic) and obstacles are looked at that show signs of epistemological, political, and institutional barriers that Bosnia and Herzegovina faces as a developing country Europeanizing its system of education.
Keywords: National Qualification Framework; education performance; university barriers; education system; Bosnia and Herzegovina